Implementation of Kohort Mother Register by Coordinator Midwife of Public Health Center in District West Kotawaringin, Central Kalimantan - Jatmiko Susilaningsih (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
The cohort register is an instrument for recording health services for pregnant women at the Public Health Center, which is a complete and continuous collection of all data. Each midwife provides services in the building and outside the building immediately takes notes. Compliance, consistency of midwives and the recording system of the Public Health Center greatly influenced the results of the data in the cohort register. A valid and reliable data source is a tool in the advocacy of policy makers in the progress of the program quickly and on target. The purpose of this study was to explore the implementation of the maternal cohort register by the midwife coordinating the Public Health Center. The research design used is descriptive qualitative. Data collection using in-depth interview techniques (depth interview) with semi-structured questions with a sample of 8 informants. The results showed that there was no Standard Operating Procedure for recording system services for pregnant women, resulting in no evaluation of service quality. The recording of K1 and K4 has been carried out. Revisits outside K1, K2, K3 and K4 and visits outside the region were not recorded in the cohort register. Data processing by grouping, tracing and validating data has not been maximal. Lack of understanding of the coordinating midwife, lack of supervision, training and evaluation from the Public Health Center and the Health Office are obstacles in the implementation of the mother cohort register by the coordinating midwife.